Quality of Life in Adolescent's Idiopathic Scoliosis before and after Physical Therapy: A Preliminary Study - Shkurta Rrecaj-Malaj; Adem Hykolli; Shendrit Lumi; Ardiana Murtezani (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2018)
Adolescent Idiopathic Scoliosis (AIS) accounts for 80% of all types of diagnosed scoliosis, occurring in 2%-3% of growing age population. This disorder is quite complicated and physical therapy is important factor in the treatment. The aim of this study is to evaluate the effi cacy of physical therapy in quality of life in adolescent idiopathic scoliosis. This research was conducted in 56 consecutive adolescent idiopathic scoliosis patients (32 females and 24 males), aged 10-17 years, Cobb angle 10º-45º, at Physical and Rehabilitation Medicine Clinic, University Clinical Center of Kosovo (UCCK), Prishtina, Kosovo, during the period 2016-2017. The physical therapy protocol, including combined Schroth and Pilates exercise were performed during 3 months. The evaluation of Quality of Life (QoL) is done by SRS-22r questionnaire at the beginning and the end of the treatment. Results displayed that supervised combined Schroth and Pilates exercises have provided benefi t to the standard of care by improving QoL before and after physical therapy in all components: the mean for function has improved from 3.15 to 3.45, pain from 3.23 to 5.54, self-image from 3.36 to 5.46, mental health from 3.01 to 3.35, and in overall QoL was improved from 3.30 to 3.68. Quality of life was signifi cantly better after physical therapy (p<0.05). The study shows that physical therapy in scoliosis patients achieves good results in daily living life.